Incident Analysis and Standardisation of Mountainous Flight Competency for Improving Flight Safety in Indonesia - Helmiadi, Megi Hudi; Nugroho, Wisnu Aji; Ramadhani, Mileniawan Januar (Langit Biru: Jurnal Ilmiah Aviasi, 2025)
Safety aspect of mountain flight in Indonesia has become main concern in recent decades, specifically as it caused several casualties each year. To mitigate this risk, in-depth understanding is required, especially related to factors that contributes to flight safety in mountainous area. Despite its urgency, to the best of authors’ knowledge, there is lack of study related to flight safety and standardisation for training program and flight crew for mountainous flight in Indonesia, even in Southeast Asia. Therefore, this work discusses the analysis of mountain flight incident occurred in Indonesia, especially in Papua. Moreover, the initiation and development of the first mountainous flight training in Indonesia is proposed to solve this issue, which will be established in Aviation Polytechnic of Jayapura, a government-based training organization for aviation personnel that could represent the mountainous flight environment for training purpose.